IN SILICO DOCKING STUDIES OF GALLIC ACID STRUCTURAL ANALOGUES AS BCL-XL INHIBITOR IN CANCER - Ulfa, Dian Maria; Arsianti, Ade; Radji, Maksum (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Apoptosis, or programed cell death, forms an important part of the cellular regulation machinery. The Bcl-2 protein family, comprising proapoptotic and antiapoptotic members, forms an important part of the cells internal apoptotic pathway. Overexpression of the antiapoptotic members of the family in a number of cancer cell lines renders them immune to apoptosis and the ability to survive under conditions of cellular stress. Inhibition of the antiapoptotic members of the Bcl-2 family like Bcl-XL is, therefore, an interesting target for the development of anticancer therapy. Methods: The structure of antiapoptotic Bcl-XL receptor (1YSG) was taken from PDB database. The 23-dimensional structure of gallic acid analogs was designed. The Lipinski properties of gallic acid analogs were calculated using molsoft. Docking studies have been carried out through Autodock 4.0 software. Results: Molecular docking analysis with gallic acid and their structural analogs showed propyl gallate, benzyl gallate, diallyl gallate, phenyl ethyl gallate, and allyl gallate are more interactive and binding strongly than gallic acid at active site of Bcl-XL. Conclusion: Further these five compounds should be considered as potential candidates for Bcl-XL inhibitor. Keywords: Apoptosis, Bcl-2, Antiapoptotic Bcl-XL receptor, Gallic acid, Docking studies.